Una aproximación sectorial al planeamiento urbanístico. La ordenación urbanística de los bienes de dominio público - Escartín Escudé, Víctor (2025)
This study will attempt to offer a systematized analysis of the different mechanisms offered by the legal system and used by the sectoral legislator to condition urban planning, with the aim of achieving a more appropriate urban planning management -and free from speculative interests- of the main categories of assets that make up the public domain.